Detection of Foot-and-Mouth Disease Virus in the Absence of Clinical Disease in Cattle and Buffalo in South East Asia - Buckle, Kelly; Bueno, Rudolfo; McFadden, Andrew; van Andel, Mary; Spence, Richard; Hamill, Carolyn; Roe, Wendi; Vallee, Emilie; Castillo-Alcala, Fernanda; Abila, Ronel; Verin, Blesilda; Purevsuren, Bolortuya; et al. (Frontiers in Veterinary Science, 2021)
Foot-and-mouth disease virus (FMDV) is widespread throughout much of the world, including parts of South East Asia. Surveillance is often limited in endemic areas, relying predominantly on passive outbreak reporting, and without full understanding of transmission dynamics. We undertook an abattoir-based field study to help elucidate the low-level epidemiology of virus in endemic settings. Serum and dry mucosal swabs were collected to evaluate the presence of FMDV RNA on the nasal, oral, and dorsal nasopharyngeal mucosal surfaces of 262 healthy cattle (n=84 in Laos; n=125 in Myanmar) and buffalo (n=48 in Laos; n=5 in Myanmar) immediately following slaughter in three slaughterhouses. Swabs were tested by the OIE/FAO World Reference Laboratory for foot-and-mouth disease (WRLFMD) using pan‐serotypic real‐time reverse transcription‐PCR (rRT‐PCR) and serum was evaluated using the FMD PrioCHECK non-structural protein (NSP) ELISA. In total, 7.3% of animals had detectable FMDV RNA in one or more of the three sites including 5.3% of nasopharyngeal swabs, 2.3% of oral swabs, and 1.5% of nasal swabs. No FMDV RNA was detected in serum. Overall, 37.8% of animals were positive for NSP antibodies. Results were comparable for Laos and Myanmar, and for both cattle and buffalo, and were not significantly different between age groups. FMDV RNA present on the oral and nasal mucosa of clinically-healthy large ruminants in Laos and Myanmar demonstrates the importance of sampling asymptomatic animals as part of surveillance, and may indicate that subclinical shedding plays a role in the epidemiology of FMD in these countries.